Determination of Anticancer from EtOAc Fraction of Spatholobus Littoralis Hassk and of Molecular Structure Prediction - Iskandar, Dodi; Widodo, Nashi; Warsito, Warsito; Masruri, Masruri; Rollando, Rollando; Afthoni, Muhammad Hilmi; Ichsan, Ichsan; Hermansyah, Adi (Majalah Obat Tradisional, 2024)
In recent years, the search for new anticancer drugs from local plants in Indonesia has become an interesting topic for research. One of the typical Indonesian local plants that have been used by the community as an anticancer traditional medicine (jamu) is Spatholobus littoralis Hassk (SLH) or better known as Bajakah. The native Dayak people of Kalimantan have used it for years for the treatment of breast cancer. In this study, the separation of single compounds from the ethyl acetate fraction of SLH stems was carried out, their molecular structure was analyzed, and anticancer bioactivity was tested. The isolation used the preparative HPLC method. The elucidation of the isolates from the ethyl acetat fraction used LCMS-MS, FTIR, and NMR. Anticancer bioactivity was determined using the MTT bioassay. The result is the acquisition of two isolates; it has been predicted that both are pseudobaptinin. The anticancer IC50 of the pseudobaptinin was 62.85 ppm, and Pseudobaptinin with impurities was 145.60 ppm.